Temporal series of infant deaths in the State of Roraima (Research, Society and Development, 2021)
The objective was to analyze the infant deaths that occurred in the State of Roraima between the years 2010 to 2017. This is an ecological study of time series, delimiting the state of Roraima, dividing into counties and time (years), through the analysis of secondary data generated from the Mortality Information System, made available by the Informatics Department of the Unified Health System. The study showed that there was no reduction in infant death, showing a positive trend (0.137 tau), although not significant (value p of 0.449). The three-year period from 2015 to 2017 had the highest average mortality rate (19.3 / 1000). Uiramutã was the county with the highest rate (47.2 / 1000), in 2017; infant mortality rates are higher in counties with indigenous populations, showing regional specificities. It is concluded that it is necessary to reformulate the state health policies, which meets the needs and the distinct specificities of the population and that guarantees equal access to public health policies.